Komunikasi Persuasif Coffee Shop melalui Strategi Experiential Marketing - Muhammad Alwan Hanif; Mustiawan; Nurlina Rahman (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2025)
This study is a study of persuasive communication strategies conducted by Niskala Coffee. Through experiential marketing, Niskala Coffee builds relationships through emotional engagement and enhances consumer experience. This phenomenon is explored using a qualitative approach with a case study method, data using interviews, observations, and documentation. Data analysis was carried out in three stages, namely reduction, presentation, and conclusion with data triangulation to maintain data validity. The results of the study indicate the success of the application of experiential marketing elements (sense, feel, think, act, and relate) in forming a unique consumer experience that is complemented by the influence of the natural environment, in this case the nearby lake, which is directly relevant to Niskala Coffee. This practice builds an intimate relationship and helps enhance the customer journey. Although contextualized to a specific setting, the evidence from this study provides a unique contribution to the development of experiential marketing in nature-based food businesses